2017 IEEE 86th Vehicular Technology Conference (VTC-Fall) 2017
DOI: 10.1109/vtcfall.2017.8288015
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a Non-Coherent Massive SIMO M-DPSK System

Abstract: In this paper, we analyze the effect of time-varying channels on the performance of a non-coherent massive singleinput multiple-output (SIMO) uplink system based on M-ary Differential Phase Shift Keying (M-DPSK), when amalgamated with bit-interleaved coded modulation relying on iterative decoding (BICM-ID). Additionally, we study the number of receive antennas (R) required in hostile time-varying channels for attaining a similar performance to that achieved for stationary channels. Furthermore, we analyze the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…However, the quality of the system is degraded as the Doppler frequency is increased, where the worst performance corresponds to f d = 1600Hz. In any case, for reasonably moderate values of f d , the performance degradation is negligible as anticipated in [10].…”
Section: Numerical Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…However, the quality of the system is degraded as the Doppler frequency is increased, where the worst performance corresponds to f d = 1600Hz. In any case, for reasonably moderate values of f d , the performance degradation is negligible as anticipated in [10].…”
Section: Numerical Resultssupporting
confidence: 53%
“…However, this scheme is implemented with single-carrier modulation (SCM), assuming that the channel is flat-fading and remains invariant over a longenough coherence time. The effect of time-varying channels is also analyzed in [10] for the case of SCM systems, where it is concluded that the non-coherent scheme is robust to fast time variability of the channel.…”
Section: Introductionmentioning
confidence: 99%
“…Even though in this paper we do not show the performance in time-varying channels, it has been shown in[24] that the non-coherent DPSK-based massive MIMO is very robust to the time variability of the channel.…”
mentioning
confidence: 67%
“…Consequently, the choice of the individual constellation is crucial to produce a robust joint-constellation against interference and noise effects. The most used constellations are the Type B [12] and equal error protection (EEP) [13]. The constellation of the -th UE can be expressed as…”
Section: Multi-user Multiplexing In the Constellation Domainmentioning
confidence: 99%